Ulnar Impaction Syndrome and TFCC Injury: Their Relationship and Management - Im, Jin-Hyung; Lee, Jin-Woo; Lee, Joo-Yup (Journal of Wrist Surgery, 2023)
Ulnar-sided wrist pain can be caused by a number of problems, including ulnar impaction syndrome (UIS) and triangular fibrocartilage complex (TFCC) injury. Multiple studies have described the diagnostic criteria for UIS and TFCC injuries, and excellent surgical outcomes have been reported for each condition. Few studies have examined the extent to which the two independent conditions cooccur, and little is known about their relationship. Based on theories in the literature and clinical experience, we propose the possibility of TFCC injury as the cause and result of UIS in this review.
Keywords: triangular fibrocartilage complex; ulnar-sided wrist pain; ulnar impaction syndrome; ulnar styloid process impaction; triangular fibrocartilage complex repair; ulnar shortening osteotomy; combined procedure